2013
DOI: 10.1021/bm401555p
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Nanotubes As Vehicles for Gene Delivery into Human Cells

Abstract: Lignin nanotubes (LNTs) synthesized from the aromatic plant cell wall polymer lignin in a sacrificial alumina membrane template have as useful features their flexibility, ease of functionalization due to the availability of many functional groups, label-free detection by autofluorescence, and customizable optical properties. In this report we show that the physicochemical properties of LNTs can be varied over a wide range to match requirements for specific applications by using lignin with different subunit co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 97 publications
1
63
0
1
Order By: Relevance
“…Caicedo et al [122] developed a method to synthesize lignin-based nanotubes (LNTs) and nanowires using an alumina membrane as a sacrificial template. After showing the ability of DNA to adsorb onto LNTs, Ten et al [123] demonstrated the potential of LNTs to be used as a gene delivery vector. The morphology and properties of the LNTs were dependent on the plant species from which the lignin originated as well as the lignin isolation procedure [123].…”
Section: Polymer-based Nanomaterials For Gene Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Caicedo et al [122] developed a method to synthesize lignin-based nanotubes (LNTs) and nanowires using an alumina membrane as a sacrificial template. After showing the ability of DNA to adsorb onto LNTs, Ten et al [123] demonstrated the potential of LNTs to be used as a gene delivery vector. The morphology and properties of the LNTs were dependent on the plant species from which the lignin originated as well as the lignin isolation procedure [123].…”
Section: Polymer-based Nanomaterials For Gene Deliverymentioning
confidence: 99%
“…After showing the ability of DNA to adsorb onto LNTs, Ten et al [123] demonstrated the potential of LNTs to be used as a gene delivery vector. The morphology and properties of the LNTs were dependent on the plant species from which the lignin originated as well as the lignin isolation procedure [123]. For example, LNTs synthesized with lignin that had been isolated from loblolly pine ( Pinus taeda L) wood with thioglycolic acid localized to the cytosol of HeLa cells, whereas LNTs synthesized from pine wood lignin isolated using NaOH penetrated the nuclei of the HeLa cells.…”
Section: Polymer-based Nanomaterials For Gene Deliverymentioning
confidence: 99%
“…36,40 This limited uptake could be likely due to the negative ζ-potential or the elongated shape: both factors may influence the interaction with cell membrane and the endosomal vesicle formation. 45,47 After 48 h of incubation, CNCs progressively penetrated in cells, with a concentration-dependent manner ( Figure 3A, middle column; Figure 3B). The merge between the fluorescent signals and the differential interference contrast (Nomarsky), which enabled us to visualize the shape of the cells in a 3D-like manner, showed spotted red circles exclusively confined to the cytoplasm.…”
mentioning
confidence: 99%
“…And from the DLS, the large size particles may be due to the agglomeration of lignin particles after centrifugation, drying and dispersed in the water ( Figure 3). Interests in using lignin micro/nano-particles for developing biodegradable materials are growing for many potential applications [16][17][18]. Many studies on lignin micro/nano-particles production used alkali lignin that was dissolved in organic solvents, such as ethylene glycol [18], acetone, tetrahydrofuran (THF) etc.…”
Section: Results and Discussion 31 Sem And Plm Observationmentioning
confidence: 99%